Der Baum der Erkenntnis: die biologischen Wurzeln des menschlichen Erkennens - Maturana, Humberto R. (Scherz, 1987)
Humberto R. Maturana, Francisco J. Varela: "Der Baum der Erkenntnis". Aus d. Span. v. Kurt Ludewig. Scherz Verlag, Bern, München, Wien 1987, 280 S., geb., 39,80 DM